An innovative design of solar-assisted carnot battery for multigeneration of power, cooling, and process heating: Techno-economic analysis and optimization. (July 2023) - Alsagri, Ali Sulaiman
Abstract: Research on large-scale energy storage systems has so far been very dedicatedly focused on electricity storage. Even for thermal energy-driven technologies, so-called Carnot batteries, larger electricity output, and higher power-to-power efficiency have been the major concerns. On the other hand, energy storage technologies are mainly useful for helping more renewable energy deployment for which recent studies show that most of the energy sectors are going through a smooth and continuous transition towards sustainability except for the industrial heating and cooling sectors. Therefore, developing energy storage solutions that can potentially contribute to this sector will be precious. This study proposes a multi-generating solar-assisted molten-salt-driven Carnot battery that is used for storing excess electricity of a PV farm in Saudi Arabia and delivering power for grid balancing, steam for process heating, as well as space heating/cooling for several industrial factories. The article presents a detailed techno-economic analysis of the system after making the configuration optimized based on multi-objective optimization techniques. The results show that such a multi-generating solar-assisted molten-salt-driven Carnot battery in the optimized configuration may result in power-to-power, power-to-process heat, and overall efficiencies of 26.82%, 55.78%, and 82.6%. With these performance factors, using standard global prices for electricity and heating, with a process heating cost of higher than 10.15 c$/kWh (which is very realistic), the system will outperform only power-generating Carnot batteries.